Evolution of support teachers towards inclusive education: an autonomous legislative perspective in Spain - Pérez-Gutiérrez, Raquel; Casado-Muñoz, Raquel; Rodríguez-Conde, María-José (Revista Complutense de Educación, 2021)
In terms of inclusion, the Spanish educational legislation in democratic times has walked since the 90s towards the real attention of the rights of all citizens, trying to respond to the principles emanating from international agreements: since the Salamanca Declaration on Special Educational Needs of 1994 to the convention on the Rights of Persons with Disabilities, in 2006. Among the support tools set by the regulations is the figure of support teachers. These teachers highlights, likewise, as a key resource in the consolidation of inclusive schools. This article intends to analyse the evolution that the professional profile of support teachers (Therapeutic Pedagogy and Hearing and Languaje) has undergone in the last decade through state and autonomical regulations from the different autonomous communities in Spain, and gather normative evidence in order to value if this evolution responds to the empirical application of an inclusive educational model. Analysis of content as an analitical method has been applied, performing a descriptive study of these professionals' functions contemplated in 62 documents of different legal status, published between the period 1998-2019. It has been noted that the functions included in the 1st state regulation dating from the 80's still prevail. Some advances in the more recent regulations can be acknowledged, in favour of educational interventions in a more natural learning context and reducing student support in controlled environments. Co-teaching between the different educational agents is emerging as an essential element for inclusion in educational centres. Suggested improvements have been provided in the adaptation of support teachers' role in inclusive schooling.
Keywords: Inclusion; support teachers; therapeutic pedagogy; legislation educational content analysis